The Effect of Both (Ballistic and Plyometric) Methods of Exercises in Protecting from Knee Joint Injury in Terms of the Most Important Muscles Working on it for the Handball Center Player - Eman Darweesh Jari 1 , Hasim Abdul-Jabar Salih 2 , Ali Hasson Jawad (Indian Journal of Forensic Medicine & Toxicology, 2020)
The knee joint injury is very common for the handball center player, because of his position, which dependson the rotation on one of the legs to shoot on the goal with or without resistance from the opponent andjumping, and this requires giving appropriate exercises to strengthen the most important muscles workingon this joint, which works to prevent injury in it through experimenting both (ballistic and plyometric)training methods, and the aim of the research is to identify the effect of both (ballistic and plyometric)methods in preventing knee joint injury according to the most important muscles working on the knee jointfor the handball center player, and to identify the best methods in preventing Knee joint injury according tothe most important muscles working on the knee joint for the research sample, and the researchers used theexperimental approach with two experimental equal groups, The research community was determined whichare the center players in Karbala governorate handball Clubs, in the youth age group (17-19) years, and theywere randomly and evenly divided into two experimental groups as a sample for research As the first groupused ballistic exercises, and the second group used plyometric exercises.